Catholicism today : an introduction to the contemporary Catholic Church - Marienberg, Evyatar (New York : Routledge, 2015)
This book is designed to address common misconceptions and frequently asked questions regarding the Catholic Church, its teachings, and the lived experience of Catholics in modern societies worldwide. Opening with a concise historical overview of Christianity in general and Catholicism in particular, the text explores the core beliefs and rituals that define Catholicism in practice, the organization of the Church and the Catholic calendar, as well as the broad question of what it means to be Catholic in a variety of cultural contexts. The book ends with a discussion of the challenges facing the Church both now and in the coming decades.--Publisher information.
A very concise history of Christianity and Catholicism -- 1. Being Catholic -- 2. Catholic belief -- 3. The Catholic Church -- 4. Catholic rituals -- 5. The Catholic calendar -- 6. Catholic challenges.
Includes bibliographical references and index.
Keywords: Catholic Church -- Doctrines; Theology, Doctrinal -- Popular works; Catholic Church -- Customs and practices